Anesthetic management of a patient with Freeman‐Sheldon syndrome undergoing oral surgery: A case report. Issue 6 (9th June 2021) - Sato (Boku), Aiji; Sento, Yoshiki; Hasegawa, Tatsuya; Tsutsumi, Kosuke; Kamimura, Yuji; So, MinHye; Kako, Eisuke; Sobue, Kazuya
Abstract: In the anesthetic management in this case was how to manage the patient without causing respiratory depression and respiratory muscle fatigue. Abstract : Preoperative chest X‐ray of this patient. The chest X‐ray showed scoliosis.